2023
DOI: 10.1093/nsr/nwad066
|View full text |Cite
|
Sign up to set email alerts
|

On the topological surface states of the intrinsic magnetic topological insulator Mn-Bi-Te family

Abstract: We review recent progress in the electronic structure study of intrinsic magnetic topological insulators (MnBi2Te4)•(Bi2Te3)n ($n\ = \ 0,\ 1,\ 2,\ 3$) family. Specifically, we focus on the ubiquitously (nearly) gapless behavior of the topological Dirac surface state observed by photoemission spectroscopy, even though a large Dirac gap is expected because of surface ferromagnetic order. The dichotomy between experiment and theory concerning this gap behavior is perhaps the most critical and puzzling question in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 131 publications
0
5
0
1
Order By: Relevance
“…然而, 在磁 子反常霍尔效应 [15−17] ; 偶数层MBT薄膜的轴子 绝缘体态拓扑磁电效应 [15,18] ; 在费米能级附近包含 一对Weyl点的理想的Weyl半金属 [15,16] ; 通过与s 波超导体 [19] 相互作用可能存在的马约拉. 这种同 时具备拓扑性和磁性的本征磁性拓扑绝缘体, 不仅 为研究拓扑磁有序结构和新颖的拓扑相变提供了 理想的平台, 而且对低功耗甚至无功耗的拓扑自旋 电子器件 [20] 、太赫兹辐射器件 [21] 及拓扑量子计算 [22] 等领域的发展起到积极推动作用, 如图1所示. 2010年, Mong等 [27] 曾理论预言存在一种本 征的反铁磁拓扑绝缘体, 即使不满足时间反演对称 性, 但当其满足时间反演Q和空间平移对t 1/2 的 联合对称性S(S = Qt 1/2 )时, 可以同时保留磁性 和拓扑性.…”
Section: 引 言unclassified
“…然而, 在磁 子反常霍尔效应 [15−17] ; 偶数层MBT薄膜的轴子 绝缘体态拓扑磁电效应 [15,18] ; 在费米能级附近包含 一对Weyl点的理想的Weyl半金属 [15,16] ; 通过与s 波超导体 [19] 相互作用可能存在的马约拉. 这种同 时具备拓扑性和磁性的本征磁性拓扑绝缘体, 不仅 为研究拓扑磁有序结构和新颖的拓扑相变提供了 理想的平台, 而且对低功耗甚至无功耗的拓扑自旋 电子器件 [20] 、太赫兹辐射器件 [21] 及拓扑量子计算 [22] 等领域的发展起到积极推动作用, 如图1所示. 2010年, Mong等 [27] 曾理论预言存在一种本 征的反铁磁拓扑绝缘体, 即使不满足时间反演对称 性, 但当其满足时间反演Q和空间平移对t 1/2 的 联合对称性S(S = Qt 1/2 )时, 可以同时保留磁性 和拓扑性.…”
Section: 引 言unclassified
“…The primary focus will be on the ARPES evidence that demonstrates the characteristic topological electronic structures of these materials. In particular, the effect of magnetic ordering, the 3D-to-2D crossover in the thin-film limit, as well as the surface/bulk doping on their electronic structures will be discussed in detail, which differentiates the manuscript from previous reviews [ 44–46 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that it is challenging to tune the out-of-plane ferromagnetic order of MnBi 2 Te 4 effectively. Wang et al attribute the lack of magnetic effects on the surface Dirac cone of the MnBi 2 Te 4 -(Bi 2 Te 3 ) n (n = 0, 1, 2, 3) to the surface magnetism reconstruction or topological surface state redistribution [28]. However, many studies have reported that the temperature at which QAHE can be achieved can be enhanced by doping [5,9,20,25,26,[29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%